Exploratory insights from the right-sided electrocardiogram following prolonged endurance exercise. Issue 8 (16th November 2016) - Lord, Rachel; George, Keith; Somauroo, John; Jain, Nikhil; Reese, Kristin; Hoffman, Martin D.; Haddad, Francois; Ashley, Euan; Jones, Helen; Oxborough, David
Abstract: Background : Prolonged strenuous exercise has a profound effect on cardiac function. The right heart may be more susceptible to this imposition; yet, right-sided chest leads have not been utilised in this setting. Methods : Thirty highly trained athletes at the 2014 Western States 100-mile Endurance Run from Squaw Valley to Auburn, California (body mass 68 ± 12 kg, age 45 ± 10 years, 57 ± 15 miles per week) were recruited for the study. Pre- and post-race, a right-sided 12-lead ECG was obtained and data were extracted for P, R and S waves, J point, ST segment and T wave amplitude. Data were compared using Students T -test and statistical significance set as P  < .05. Results : There was a significant increase in P wave amplitude (29%) and QTc interval (4%) pre- to post-race from standard 12-lead ECG. From the right-sided12-lead ECG, a 23% ( P  = .01) and 38% ( P  = .03) increase in J point amplitude in V1R and V2R and a 22% ( P  = .05) increase in ST segment integral in V2R and V3R were evident. T wave inversion was evident in leads V2R–V6R in 50–90% of athletes, respectively. Close examination revealed marked heterogeneity in individual ECGs. Conclusions : Completion of a 100-mile ultra-marathon resulted in significant changes in the right-sided ECG alongside more marked responses in specific individuals. P wave, ST segment and T wave changes post-race are indicative of acute exercise-induced right heart electrical adaptation.